2020
DOI: 10.1016/j.econedurev.2020.101981
|View full text |Cite
|
Sign up to set email alerts
|

Boys lag behind: How teachers’ gender biases affect student achievement

Abstract: Boys Lag Behind: How Teachers' Gender Biases Affect Student Achievement * I use a combination of blind and non-blind test scores to show that middle school teachers favor girls when they grade. This favoritism, estimated in the form of individual teacher effects, has long-term consequences: as measured by their national evaluations three years later, male students make less progress than their female counterparts. Gender-biased grading accounts for 21 percent of boys falling behind girls in math during middle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(47 citation statements)
references
References 38 publications
3
43
0
1
Order By: Relevance
“…Moreover, by uti-lizing independently collected test scores as outcome measures, we evaluate the impact of teacher's bias on actual learning outcomes. Thus, our analysis is different from some other studies in the literature that look at discrimination in grading induced by teacher's biased beliefs (Lavy, 2008;Lavy and Sand, 2018;Terrier, 2020).…”
Section: Introductionmentioning
confidence: 60%
“…Moreover, by uti-lizing independently collected test scores as outcome measures, we evaluate the impact of teacher's bias on actual learning outcomes. Thus, our analysis is different from some other studies in the literature that look at discrimination in grading induced by teacher's biased beliefs (Lavy, 2008;Lavy and Sand, 2018;Terrier, 2020).…”
Section: Introductionmentioning
confidence: 60%
“…The seriousness of maths achievement gaps by gender and race are widely recognized (Lavy, 2008;Burgess and Greaves, 2013;Cornwell et al, 2013;Campbell, 2015;Terrier, 2016), and considerable progress has been made towards understanding the impact of teacher expectations and bias in high school and university course enrolment, occupational choices and earnings in adulthood (Lavy, 2008;Mechtenberg, 2009;Lavy and Sand, 2018). We find that accounting for socioeconomic background, cognitive ability and student behaviours, the teacher-test score gap for a child with obesity is of similar magnitude (0.22 to 0.28 SD) to the size of the teacher-test score gap against girls in our data (0.20 to 0.22 SD).…”
Section: Discussionmentioning
confidence: 99%
“…Borrowing from the larger literature on teacher-test score gaps by gender, there is empirical evidence of a teacher-test score gap in maths but not literacy (e.g. in France, Terrier, 2016). It has been suggested that teachers hold a belief that maths (but not literacy) is more difficult for girls than boys due to an assumed inferior ability in this area (e.g.…”
Section: Non-blind Teacher Assessments and Blind Test Scoresmentioning
confidence: 99%
“…Teachers also grade boys less favorably even when their performance is equal to girls' in reading, math, and science tests (Cornwell et al 2014). Their gender biases in favor of girls have a strong impact on girls' progress in both math and literacy (Terrier 2016). However, when girls and boys have similar levels of achievement, they give girls' mathematical skills a lower rating than boys' skills (Cimpian et al 2016).…”
Section: And Behavior Problemsmentioning
confidence: 99%